Cluster Preface: Organosulfur and Organoselenium Compounds in Catalysis - Yeung, Ying-Yeung (Synlett, 2019)
Ying-Yeung Yeung received his B.Sc. (2001) at The Chinese University of Hong Kong. He continued his graduate research at the same university under the supervision of Prof. Tony K. M. Shing. After four years (2001–2005) of research dedicated toward natural product synthesis, he moved to the USA to conduct postdoctoral research with Prof. E. J. Corey at Harvard University (2005–2008). In 2008, he joined the National University of Singapore, Department of Chemistry. In 2015, he moved to The Chinese University of Hong Kong as an associate professor. He has been the department chairman (since 2016) and a full professor (since 2019). His research interests include asymmetric catalysis, green oxidation, and methodology development.